The genus Adelius Haliday, 1833 in the fauna of Korean Peninsula (Hymenoptera: Braconidae: Cheloninae: Adeliini) - Belokobylskij, Sergey A.; Lee, Hye-Rin; Ku, Deokseo (Zootaxa, 2024)
The species of the genus Adelius Haliday, 1833 found in the Korean Peninsula are reviewed. A new species Adelius myriolus sp. nov. is described and illustrated. The illustrated redescription of Adelius amplus Belokobylskij, 1998 and a key to four known Korean Adelius species are provided.